Analysis of Oil Content in Water and Sediment in Belakang Padang Coastal Waters 0f Batam Riau Archipelago Province - Hutagaol, Denny B; Amin, Bintal; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in September 2015 in the coastal waters of Belakang Padang, Batam Riau Archipelago Province to analyze the concentration of oil in the water and sediment, the difference and the relationship between oil concentration in the water and in the sediment. Water samples were taken by using sample bottles and sediment samples were taken by using Ekman grab from 15 sampling sites, and then they were analyzed in the Marine Chemistry Laboratory University of Riau. The highest concentration in the water was found in Station 2 (0.1823 ppm) and the lowest in Station 3 (0,1328ppm). The highest oil concentration in the sediment was in Station 2 (286 ppm) and the lowest in Station 3 (130 ppm). The concentration of oil in the sediment were higher than in water. Oil concentration in the water and in sediment has weak relationship and negatively correlated. Characteristics of the sediment in the sampling sites was dominated by sand fraction.   Key words :Oil, Sediment, Water, Batam